Swertia patnitopiansis, a new species of Gentianaceae from North-Western Himalaya, India - Singh, Bikarma (Phytotaxa, 2021)
Swertia patnitopiansis (Gentianaceae), a new species from Patnitop Hill, North-Western Himalaya, India is described. This new species is morphologically similar to S. cordata but differs in certain characters, which are discussed below. The population mapping and threat assessment was undertaken for the new species and the species classified as Critically Endangered.